Internal Governance Challenges and Nigeria’s International Relations Goals - AGBAENYI, Alexander Nnaemeka; OKONKWO, Nnamdi (Socialscientia: Journal of Social Sciences and Humanities, 2025)
Nations enhance their overall development and global standings through international relations. Nigeria’s poor conditions of development and international image crisis worry scholars and other stakeholders of African politics considering its high participation status in foreign relations. Accusing fingers are directed at internal factors vis-a-vis foreign relations. The paper examines the complex interplay between Nigeria’s internal governance challenges and the weakness in attaining international relations goals. The paper is a qualitative research. It used a mixed-method approach of data collection dwelling on in-depth interviews and published data from relevant sources. A purposive sampling technique was used to select interview respondents. The paper adopted the liberal institutionalism theory for explanation. As a critique of realist military power and state-centric perception of international relations, Robert Keohane and Joseph Nye, Jr underscored the roles of international institutions, cooperation, and governance in attaining national and international goals. They argue that national governance composition considerably influences a country’s capacity to pursue efficient international relations and achieve targeted goals. The theory posits that states are not only anxious about power, but they are also anxious about achieving mutually beneficial gains through cooperation. Findings show that Nigeria is a major socio-economic and political interest in Sub-Sahara Africa and has recorded enormous engagements in the global international system over the decades. However, its foreign relations are undermined by internal governance deficiencies that led to collaborated imperialism, fraud, and mismanagement of public resources; international image crisis, and stringent living conditions for Nigerians and the failure to exploit global interconnectivity and interdependence of economies, politics, and culture.